Trauma web-based psychoeducational programme: systematic cultural adaptation and protocol for a feasibility-acceptability study - Indira Primasari; Chris M. Hoeboer; Marit Sijbrandij; Miranda Olff (European Journal of Psychotraumatology)
Background: Trauma exposure in Indonesia is high despite the fact that there is limited accessibility to mental healthcare. Pulihkan Luka (PL) is a web-based trauma psychoeducation intervention that aims to provide a practical solution to overcome barriers to accessing mental healthcare.Objectives: This article aimed to (1) describe the cultural adaptation process of PL for Indonesian students and (2) describe the design of the pilot randomised controlled trial (RCT) that examines the feasibility and acceptability of PL.Methods: First, we describe the cultural adaptation process of PL following the 5-phase Formative Method for Adapting Psychotherapy (FMAP) approach: (1) knowledge generation, (2) information integration, (3) review and revision, (4) mini-testing, and (5) finalisation. Focus Group Discussion (FGD) was conducted to gather the views of 15 stakeholders on psychoeducation material and trauma-related mental health problems. Based on the outcomes, we decided to utilise the informal Indonesian language, incorporate practical worksheets and infographics, which include illustrations that reflect Indonesia’s cultural diversity, and provide guidance on seeking help that aligns with the mental health system in Indonesia. Second, we describe the design of a pilot RCT. Undergraduate students (N = 130) will be randomised to (1) four to seven sessions of PL + Enhanced Usual Care (PL + EUC; n = 65) or (2) Enhanced Usual Care only (EUC only; n = 65). Assessments will be conducted at baseline, post-intervention, and three and six-month follow-up. Additionally, 20 participants will be invited for an FGD to explore their experiences with the intervention. Quantitative data will be analysed using linear mixed-effect models, and qualitative data will be analysed using thematic analysis.Discussion: Cultural adaptation is crucial for optimally developing and assessing the feasibility and acceptability of a web-based trauma psychoeducation intervention in Indonesia. The outcomes of the RCT will inform the feasibility and acceptability of web-based trauma psychoeducation in the Indonesian undergraduate student population.